Pressure dependence of side chain 13C chemical shifts in model peptides Ac-Gly-Gly-Xxx-Ala-NH2 - Beck Erlach, Markus; Koehler, Joerg; Crusca, Edson [UNESP]; Munte, Claudia E.; Kainosho, Masatsune; Kremer, Werner; Kalbitzer, Hans Robert (My University, 2017)
For evaluating the pressure responses of folded as well as intrinsically unfolded proteins detectable by NMR spectroscopy the availability of data from well-defined model systems is indispensable. In this work we report the pressure dependence of 13C chemical shifts of the side chain atoms in the protected tetrapeptides Ac-Gly-Gly-Xxx-Ala-NH2 (Xxx, one of the 20 canonical amino acids). Contrary to expectation the chemical shifts of a number of nuclei have a nonlinear dependence on pressure in the range from 0.1 to 200 MPa. The size of the polynomial pressure coefficients B1 and B2 is dependent on the type of atom and amino acid studied. For HN, N and Cα the first order pressure coefficient B1 is also correlated to the chemical shift at atmospheric pressure. The first and second order pressure coefficients of a given type of carbon atom show significant linear correlations suggesting that the NMR observable pressure effects in the different amino acids have at least partly the same physical cause. In line with this observation the magnitude of the second order coefficients of nuclei being direct neighbors in the chemical structure also are weakly correlated. The downfield shifts of the methyl resonances suggest that gauche conformers of the side chains are not preferred with pressure. The valine and leucine methyl groups in the model peptides were assigned using stereospecifically 13C enriched amino acids with the pro-R carbons downfield shifted relative to the pro-S carbons.
Keywords: 13C shifts; Biosynthetically labeled; High pressure NMR; Pressure coefficients; Random coil peptides; Stereospecific assignment